آثار الاستثمار على الاقتصاد العراقي: The impact of investment on the Iraqi economy - ناجي ساري فارس, (Journal of North African Economies, 2025)
Studies and research have shown that investment has a number of benefits that accrue to the national economy. Indeed, it has become a tool for achieving economic and social goals. One of the most important goals is achieving development dimensions, creating job opportunities to reduce unemployment and poverty, attracting foreign currencies, as well as attracting national migratory capital. It contributes to the transfer and localization of advanced technology from developed countries by attracting foreign investments, especially direct, and by providing infrastructure. In addition, the presence of policies and procedures affects the advancement of the unilateral Iraqi economic reality. By contributing to investment projects that lead to the revitalization of the agricultural, industrial and tourism sectors and the development of tourist facilities to diversify sources of income. Accordingly, investment has positive effects in transferring scientific methods in management and production. Investment also affects the development and development of infrastructure, represented by various service facilities, electricity stations, water and sewage networks, and roads. Likewise, investment has positive effects in increasing sectoral interactions, achieving human development and developing the skills of workers in different economic sectors.